Teaching English Language Using Total Physical Response Method - Bakhtiyarovna, Madina Umirqulova (Miasto Przyszłości, 2024)
In children`s development early years play an important role. Physical, emotional, cognitive and language development progress very fast. It is very period to start teaching vocabulary either for L1 or L2 languages. For this, there are a lot of methods and techniques but the most appropriate one is Total Physical Response (TPR) method. According to Richards and Rodgers (2001), TPR is the method in which teaching will rely on actions, activities and coordination of speech. Because there is no texting, vocabulary can be taught through using songs, images and games, which include actions. In this literature review comparison of scholars view about how to teach vocabulary using TPR method will be discussed and analyzed.